2021
DOI: 10.3389/fphys.2021.628502
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning in Automatic Sleep Staging With a Single Channel Electroencephalography

Abstract: This study centers on automatic sleep staging with a single channel electroencephalography (EEG), with some significant findings for sleep staging. In this study, we proposed a deep learning-based network by integrating attention mechanism and bidirectional long short-term memory neural network (AT-BiLSTM) to classify wakefulness, rapid eye movement (REM) sleep and non-REM (NREM) sleep stages N1, N2 and N3. The AT-BiLSTM network outperformed five other networks and achieved an accuracy of 83.78%, a Cohen’s kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…To confirm the validity of the control sample, other studies used the same database [ 10 , 77 , 78 , 79 , 80 , 81 , 82 ], including with FM population [ 83 ]. Alterations in functional connectivity are frequent in patients with FM (Hargrove et al, 2010), in particular alterations in frontotemporal connectivity [ 62 , 65 , 84 ], and are often associated with a lower white matter volume than in controls in frontal regions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the validity of the control sample, other studies used the same database [ 10 , 77 , 78 , 79 , 80 , 81 , 82 ], including with FM population [ 83 ]. Alterations in functional connectivity are frequent in patients with FM (Hargrove et al, 2010), in particular alterations in frontotemporal connectivity [ 62 , 65 , 84 ], and are often associated with a lower white matter volume than in controls in frontal regions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain leaves a footprint: experiencing chronic pain can cause anatomical and functional reorganization of the brain [ 8 ], as shown in several disorders such as phantom pain, chronic back pain, irritable bowel syndrome, and FM (May, 2008). The morphological changes include the loss of gray matter volume [ 9 ], whereas the functional alterations include aberrant functional activity [ 10 ]. Recent reviews of the long-term effects of chronic pain have demonstrated the appearance of a “brain signature” [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The achieved 79.7 % (κ = 0.73) scoring accuracy compares favorably to the recent advances in the deep learning-based automatic sleep scoring presented in the literature. Based on standard EEG recordings, several deep learning models with different architectures have achieved an accuracy of 82.9-86.2 % (κ = 0.77-0.80) [10], [15], [17], [21], [22] with single-channel inputs. Furthermore, a random forest classifier has been used to achieve 72.98 % accuracy based on a single frontal EEG channel [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that electrode selection in single-channel-based automated staging is also an essential factor affecting the correct rate. Some studies have used F4-M1 channels [ 23 ], and others have used Pz-Oz channels, or Fpz-Cz channels, and staging based on prefrontal FP1 and FP2 channels [ 24 , 25 , 26 , 27 ]. Ghimatgar et al revealed that the results of sleep stage staging using Fpz-Cz EEG signals were more accurate than other channels [ 21 ].…”
Section: Inductionmentioning
confidence: 99%